CRISPR/Cas9 ADCY7 Knockout Stimulates the Insulin Secretion Pathway Leading to Excessive Insulin Secretion - Alhaidan, Yazeid; Christesen, Henrik Thybo; Lundberg, Elena; Balwi, Mohammed A. Al; Brusgaard, Klaus (Frontiers in Endocrinology, 2021)
Aim Despite the enormous efforts to understand Congenital hyperinsulinism (CHI), up to 50% of patients are found negative in the known pathogenic genes. This poses a challenge for both the geneticist and physician for targeted treatment. We aimed to screen a genetic cause of CHI. Patient A nonsyndromic, Swedish Caucasian boy presented four months old with hypoglycemic convulsions and loss of consciousness. Methods Genetic screening was performed with a trio based whole-exome sequencing (WES). Gene knockout in the RIN-m cell line was established by CRISPR/Cas9and the expression of the related gene was performed using real-time PCR. Results WES revealed compound heterozygous variants in the Adenylyl Cyclase 7 (ADCY7) gene. A paternal (p.Asp439Glu) and a maternal (p.Gly1045Arg) variants located in the cytoplasmic domains (C1 and C2) in a highly conserved and functional amino acid region. Genetic expression analysis indicated that Adcy7 loss of function leads to an extreme increase in mRNA levels of the insulin regulator genes, Ins1 and Ins2, as well as glucose uptake and sensing Solute Carrier Family 2 Member 2 (Scl2a2) and Glucokinase (Gck) via upregulation of Pancreatic and duodenal homeobox 1 (Pdx1), and Forkhead Box Protein A2 (Foxa2) genes leading to the activation of the glucose stimulated-insulin secretion (GSIS) pathway. In addition, modified cells show a significant increase in insulin secretion reaching 54% and 49% at low and high glucose concentrated media compare to wild-type, respectively. Conclusion This study identified a novel gene ADCY7 to cause CHI via activating the GSIS pathway.